2009
DOI: 10.1007/s11120-009-9468-5
|View full text |Cite
|
Sign up to set email alerts
|

Alternative methods for sampling and preservation of photosynthetic pigments and tocopherols in plant material from remote locations

Abstract: Current methods for the study of pigments involve freezing in liquid nitrogen and storage at -80 degrees C or lyophilization until HPLC analysis. These requirements greatly restrict ecophysiological research in remote areas where such resources are hardly available. We aimed to overcome such limitations by developing several techniques not requiring freezing or lyophilization. Two species with contrasting foliar characteristics (Olea europaea and Taraxacum officinale) were chosen. Seven preservation methods we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…Samples were placed in porous tea bags and preserved in a silica gel desiccant in an opaque container for up to 3 months until pigment extraction (Esteban et al. ). Each sample was homogenized by grinding with a mortar and pestle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were placed in porous tea bags and preserved in a silica gel desiccant in an opaque container for up to 3 months until pigment extraction (Esteban et al. ). Each sample was homogenized by grinding with a mortar and pestle.…”
Section: Methodsmentioning
confidence: 99%
“…To estimate how accurately plot-level indices represent actual leaf-level pigment content, leaves and stems (n = 213) of the dominant vascular species in a subset of the sampled plots were collected at early, peak, and late season for chlorophyll and carotenoid analysis. Samples were placed in porous tea bags and preserved in a silica gel desiccant in an opaque container for up to 3 months until pigment extraction (Esteban et al 2009). Each sample was homogenized by grinding with a mortar and pestle.…”
Section: Vegetation Pigment Concentrationmentioning
confidence: 99%
“…xanthophyll cycle pigments (VAZ) and β-carotene on a chlorophyll content basis] were determined in three fully-expanded leaflets from 7 seedlings for each experimental group. Leaflet discs were collected and stored in paper envelopes filled with silica gel until extraction and transported to the analytical laboratory [65]. Photoprotective pigment pools were separated by HPLC (Waters Corp., Milford, MA, USA), following pigment extraction in cool acetone.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, previous studies have suggested that drying processes that require longer time lengths to dehydrate the seaweed samples tended to have a loss in phlorotannins and antioxidant capacity due to degradation and oxidation. 9,27 Both suggestions of the small particle size and minimum time duration of dehydration, likely explains why the dehydrated samples expressed the highest yield of phlorotannins using the DMBA assay.…”
Section: Discussionmentioning
confidence: 99%